2000
DOI: 10.1099/00221287-146-4-935
|View full text |Cite
|
Sign up to set email alerts
|

Six putative two-component regulatory systems isolated from Lactococcus lactis subsp. cremoris MG1363 The GenBank accession numbers for the sequences of the six 2CSs and surrounding ORFs determined in this work are AF172649, AF176556, AF178425, AF172650, AF176557 and AF176809 for systems A–F, respectively.

Abstract: The genetic elements specifying six putative two-component regulatory systems (2CSs) were identified on the chromosome of Lactococcus lactis MG1363. These 2CSs appear to represent distinct loci, each containing a histidine kinase and response-regulator-encoding gene pair. Transcriptional analysis of the six 2CSs was performed either by generating transcriptional fusions to a reporter gene or by primer extension. Two of the systems appeared to be expressed constitutively at a high level, whilst the remaining fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 48 publications
0
54
2
Order By: Relevance
“…lactis. Disrupting the gene for CesR led to a reduction in the ability to resist salt and osmotic stresses (66). The authors could not generate a CesS mutant, probably because that mutation was lethal.…”
Section: Mechanosensitive Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…lactis. Disrupting the gene for CesR led to a reduction in the ability to resist salt and osmotic stresses (66). The authors could not generate a CesS mutant, probably because that mutation was lethal.…”
Section: Mechanosensitive Channelsmentioning
confidence: 99%
“…The involvement of TCSs in stress responses in LAB has been evidenced mainly by phenotypic analyses of TCS-defective mutants (60)(61)(62)(63)(64)(65)(66)(67). Inactivation of homologous TCSs often results in different phenotypes, suggesting that they have different physiological roles.…”
Section: Two-component Systemsmentioning
confidence: 99%
“…LiaRS has also been identified as upregulating dltA expression in Streptococcus gordonii (149). CesSR (also referred to as TCS-D) (141,150) is an LiaRS homologue found in L. lactis. Upstream of cesSR is llmg1650, an liaF homologue.…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 99%
“…The fact that the arginine degradative pathway is involved in a range of diverse cellular functions such as energy production, acid stress resistance, and pyrimidine biosynthesis could explain the presence of such a complex regulatory circuit. Interestingly, O'Connell-Motherway et al (36) have reported on an essential two-component system that is involved in activation of arginine degradation. Whether and how this system is responsible for some of the effects described above remain to be elucidated.…”
Section: Vol 186 2004 Regulation Of Arginine Metabolism In L Lactimentioning
confidence: 99%